Understanding the role of personal development in undergraduates - Nida Zafar, (Pakistan Review of Social Sciences (PRSS), 2020)
Sociologist G. H. Mead’s renowned theory on self-development and social behaviorism proposed that the self was composed of a self-image and self-awareness, which was a part of an individual’s greater personality. This personality is a product of personal and social experience, and interaction. For this study, the process of personal development is viewed through this spectrum within a university environment. The purpose of this study is understanding the role of personal development in academia, and undergraduates’ future employability prospects by factoring into the opportunities and challenges it presents. This study aims to determine how personal development undertaken by undergraduates at Iqra University Islamabad, serves as a foundation for students to build on their personal and academic development, and discover their career pathways. Selecting a sample of respondents from the academic year of 2018, this study investigates the response of 90 first semester undergraduates. It advances on data gathered through a student answered survey, uncovering students’ response, feedback, and challenges.